PENERAPAN MODEL KOOPERATIF TIPE STAD UNTUK MENINGKATKAN KEMAMPUAN PEMBELAJARAN PKN SISWA KELAS VI SDN 018 KUOK - Darnayus Darnayus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The aim of this classroom action research was to improve the student’s ability in PKN. The sample respondents were 17 students of SDN 018 Kuok. Before the treatment was conducted, the sample was given pre-test and after the treatment, post-test was also held. The results showed that the application of the STAD type cooperative learning model with cycle 1 of the disciplinary aspects of student learning activity 73.45; learning readiness 72,75; courage 74,10; responsibility aspects 85.75; learning readiness 84.44; courage 86.41; responsibility 83.05 and understanding of tasks 85.19 while the behavior of group work activities cooperation aspects 69.44; solve problems 66.66; confidence 63.89 and the work of the group 86.11, the second cycle increased cooperation 86.11; solve problems 86.11; self-confidence 83.33 and group work results 97.22 while the learning outcomes of the first cycle of 52.94% experienced an increase of 94.12% and the average class 72.33 increased in cycle 2 to 84.47. So, the application of the STAD type cooperative learning model can improve the behavior of student learning activities and the behavior of group work activities at each meeting so that student learning outcomes also increase.